Parental Investments and Educational Outcomes: Trivers–Willard in the U.S. - Hopcroft, Rosemary L.; Martin, David O. (Frontiers in Sociology, 2016)
In the U.S. there is evidence of a Trivers-Willard (T-W) effect in educational attainment, such that the sons of high status fathers attain more education than the daughters, and the daughters of low status fathers attain more education than the sons. This paper seeks to uncover the mechanisms by which this T-W effect occurs. Data are from the High School and Beyond Study by the U.S. National Center for Education Statistics. Results show that the T-W effect is not a result of the fact that fathers are less likely to be present in the homes of children of low status fathers. Other results show that the sons of high status fathers are more likely than daughters to be sent to private high school, while the daughters of low status fathers are more likely than sons to be sent to private high school. These parental investments pay off, as the sex gap in academic GPAS (favoring women) is narrower for the children of high status fathers than the children of low status fathers. In turn, academic GPA in high school helps explain the T-W effect in educational attainment. Parental non-financial investment as measured by student academic expectations as sophomores in high school also helps explain why the sons of high status fathers obtain higher degrees than the daughters. Together, these two factors: student’s academic GPA in high school and his /her expectations of educational attainment, fully explain the T-W effect in educational attainment in the U.S.